Penerapan Nilai-Nilai Ajaran Sunan Gunung Jati Dalam Pembelajaran Berdiferensiasi Untuk Mewujudkan Pendidikan Inklusif - Maulana Yusuf Arrasuly, Sariyatun, Wildhan Ichzha Maulana (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2026)
The purpose of this article is to explore the application of the values taught by Sunan Gunung Jati in differentiated learning as an effort to realize inclusive education in Indonesia. Inclusive education emphasizes the importance of providing equal access to education for all students, icluding those with special needs, while differentiated learning is a pedagogical strategy designed to accommodate differences in learning styles, interests, and abilities of students. The values taught by Sunan Gunung Jati, such as respect for diversity, social concern, justice, and moral-based education, align with the principles of inclusive education and can serve as a strong philosophical foundation in learning practices. Using a descriptive qualitative approach, data was collected through interviews with teachers, students and parents, as well as observations and documentation in several high schools in Cirebon that have inplemented differentiated learning. The research findings indicate that the integration of the values of Sunan Gunung Jati in differentiated learning not only strengthens students’ character but also creates a more inclusive and meaningful learning atmosphere. Despite facing challenges such as resource limitations, lack of teacher understanding, and rigid curriculum, support from the school community and teacher training have proven to be important factors in the successful implementation. This study recommends enhancing educators’ understanding of local values and implementing differentiation strategies to strengthen fair and socially just education in Indonesia. Keywords : Inclusive Education, Differentiated Learning, Diversity, Sunan Gunung Jati